A New Composite Integrative and Conjugative Element Mediates Multiple Drug Resistance from Streptococcus anginosus to Streptococcus agalactiae - Wang Y; Liu T; Yi S; Zhu Y (Infection and Drug Resistance)
Yingting Wang,1,* Taoran Liu,1,* Sida Yi,2 Yuanting Zhu3,4 1Department of Critical Care Medicine, The First Affiliated Hospital, Sun Yat-Sen University, Guangzhou, 510080, People’s Republic of China; 2Institute of Antibiotics, Huashan Hospital, Fudan University, Shanghai, People’s Republic of China; 3NHC Key Laboratory of Assisted Circulation, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, 510080, People’s Republic of China; 4Department of Cardiology, The Seventh Affiliated Hospital of Sun Yat-Sen University, Shenzhen, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuanting Zhu, Department of Cardiology, The Seventh Affiliated Hospital of Sun Yat-Sen University, Shenzhen, People’s Republic of China, Tel +86-18501230142, Email zhuyuanting@sysush.comIntroduction: Integrative and conjugative elements (ICEs) are a category of horizontal mobile genetic elements (MGEs) that play important roles in mediating the spread of antimicrobial resistance in Streptococci.Methods: In this study, a novel ICE, namely ICESan 26_rplL, was identified from commensal Streptococcus anginosus through routine silico analyses. The genetic characterization of ICESan 26_rplL was explored based on a comparison with known ICEs. The cyclization and cross-species transferability (from Streptococcus anginosus to Streptococcus agalactiae) of ICESan 26_rplL were explored using inverse PCR and conjugation transfer experiments.Results: ICESan 26_rplL is 61.618 kb in length at downstream of rplL and carries multiple antibiotic resistance genes, including erm(B) [for erythromycin, clindamycin, and streptococcin B (MLSB)], tetM-tetL (tetracycline), lnu and lsa(E) (clindamycin), and ant(6)-I (aminoglycosides). The comparative analysis results showed that ICESan 26_rplL was a composite ICE with a mosaic structure composed of modules in the ICESa2603 and TnGBS families. The inverse PCR results demonstrated that ICESan 26_rplL could be excised from the chromosome to form a circular intermediate. The conjugation transfer experiment and sequencing results confirmed the cross-species transfer of ICESan 26_rplL to S. agalactiae recipients at a relatively low frequency (2.13 × 10− 8). Moreover, core functional modules were retrieved from GenBank to search for any ICEs related to ICESan 26_rplL. Eventually, 53 putative ICEs were identified, including three composite ICEs with high similarity to ICESan 26_rplL, three ICEs in the TnGBS family, and 47 ICEs in the ICESa 2603 family.Discussion: In this study, a novel mosaic ICE was reported for the first time. In addition, its transfer to the major pathogen Streptococcus agalactiae was characterized and proved. These findings suggest that this ICE is expected to become a vehicle for the dissemination of multiple antimicrobial resistance through the wider pathogen Streptococci.Keywords: Streptococcus anginosus, Streptococcus agalactiae, ICEs, antibiotic resistance genes, conjugation transfer, composite